PLGA Based Drug Carrier and Pharmaceutical Applications - Pereira, Maria Carmo; Loureiro, Joana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Poly(lactic-co-glycolic acid) (PLGA) is one of the most successful polymers used for producing therapeutic devices, such as drug carriers (DC). PLGA is one of the few polymers that the Food and Drug Administration (FDA) has approved for human administration due to its biocompatibility and biodegradability. In recent years, DC produced with PLGA has gained enormous attention for its versatility in transporting different type of drugs, e.g., hydrophilic or hydrophobic small molecules, or macromolecules with a controlled drug release without modifying the physiochemical properties of the drugs. These drug delivery systems have the possibility/potential to modify their surface properties with functional groups, peptides, or other coatings to improve the interactions with biological materials. Furthermore, they present the possibility to be conjugated with specific target molecules to reach specific tissues or cells. They are also used for different therapeutic applications, such as in vaccinations, cancer treatment, neurological disorder treatment, and as anti-inflammatory agents. This book aims to focus on the recent progress of PLGA as a drug carrier and their new pharmaceutical applications.